Pediatricians' attitudes, experience and referral patterns regarding complementary/alternative medicine: a national survey - Thomas Ronald; Sawni Anju (BMC, 2007)
Abstract Background To assess pediatricians' attitudes toward & practice of Complementary/Alternative Medicine (CAM) including their knowledge, experience, & referral patterns for CAM therapies. Methods An anonymous, self-report, 27-item questionnaire was mailed nationally to fellows of the American Academy of Pediatrics in July 2004. 648 of 3500 pediatricians' surveyed responded (18%). Results The median age ranged from 46-59 yrs; 52% female, 81% Caucasian, 71% generalists, & 85% trained in the US. Over 96% of pediatricians' responding believed their patients were using CAM. Discussions of CAM use were initiated by the family (70%) & only 37% of pediatricians asked about CAM use as part of routine medical history. Majority (84%) said more CME courses should be offered on CAM and 71% said they would consider referring patients to CAM practitioners. Medical conditions referred for CAM included; chronic problems (headaches, pain management, asthma, backaches) (86%), diseases with no known cure (55.5%) or failure of conventional therapies (56%), behavioral problems (49%), & psychiatric disorders (47%). American born, US medical school graduates, general pediatricians, & pediatricians who ask/talk about CAM were most likely to believe their patients used CAM (P < 0.01). Conclusion Pediatricians' have a positive attitude towards CAM. Majority believe that their patients are using CAM, that asking about CAM should be part of routine medical history, would consider referring to a CAM practitioner and want more education on CAM.